1999
DOI: 10.1093/toxsci/47.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct epithelial cells exposed to alpha-naphthylisothiocyanate produce a factor that causes neutrophil-dependent hepatocellular injury in vitro

Abstract: The acute hepatotoxicity induced by alpha-naphthylisothiocyanate (ANIT) in rats is manifested as neutrophil-dependent necrosis of bile duct epithelial cells (BDECs) and hepatic parenchymal cells. This hepatotoxicity mirrors that of drug-induced cholangiolitic hepatitis in humans. Since BDECs are primary targets of ANIT-induced toxicity, we hypothesized that after exposure to ANIT, BDECs produce a factor(s) that causes neutrophil chemotaxis and neutrophil-dependent hepatocellular injury. To test this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…Results of this study suggest cells of medaka intrahepatic biliary system respond to ANIT, and that responses, both cellular and system level, are similar to those described in rodents Carpenter-Deyo et al 1991;Connolly et al 1988;Hill et al 1999;Kossor et al 1993;Lesage et al 2001;Orsler et al 1999;Waters et al 2001). Changes observed in vivo, and confirmed with ex-vivo analyses (histological, immunohistochemical, ultrastructural), were; attenuation and dilation of bile canaliculi, bile preductular lesions, hydropic vacuolation of hepatocytes and BPDECs, BPDEC cytomegaly, and hyperplasia of BECs in the hilar and peri-hilar region of the liver.…”
Section: Discussionsupporting
confidence: 69%
“…Results of this study suggest cells of medaka intrahepatic biliary system respond to ANIT, and that responses, both cellular and system level, are similar to those described in rodents Carpenter-Deyo et al 1991;Connolly et al 1988;Hill et al 1999;Kossor et al 1993;Lesage et al 2001;Orsler et al 1999;Waters et al 2001). Changes observed in vivo, and confirmed with ex-vivo analyses (histological, immunohistochemical, ultrastructural), were; attenuation and dilation of bile canaliculi, bile preductular lesions, hydropic vacuolation of hepatocytes and BPDECs, BPDEC cytomegaly, and hyperplasia of BECs in the hilar and peri-hilar region of the liver.…”
Section: Discussionsupporting
confidence: 69%
“…In fact, BECs are the primary targets of ANIT-induced toxicity and injury to these cells occurs prior to hepatocellular damage [Connolly et al, 1988]. Furthermore, it has been demonstrated that after exposure to ANIT, BECs produce a factor(s) that causes neutrophil chemotaxis and neutrophil-dependent hepatocellular injury [Hill et al, 1999]. A recent study has demonstrated that human BECs exposed to certain proin¯ammatory cytokines (IL-1 and TNFa) rapidly express IL-8 and monocyte chemotactic protein-1 (MCP-1), potent chemotactic agents for neutrophils and monocytes or T cells, respectively [Morland et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results indicate that the impairment of mitochondrial biogenesis, rather than oxidative injury and mitochondrial oxidative phosphorylation, is a critical event at this stage of ANIT-induced cholestasis. The activity of antioxidant enzymes, ATP synthesis and mtDNA copy number remained unchanged after resveratrol treatment in ANIT-intoxicated rats, implying that the antioxidant properties and mitochondrial protection of resveratrol The release of cytotoxic and inflammatory mediators, including those that attract neutrophils, has been suggested to contribute to the hepatic injury induced by ANIT; however, the exact mechanisms are not well understood [27][28][29] . In the present study, an enhancement in the hepatic activity of MPO, an index of tissue neutrophil infiltration, occurred after ANITinduced liver injury.…”
Section: Wwwchinapharcom Wang T Et Almentioning
confidence: 99%